Malaysia Economic Monitor, November 2011 : Smart Cities - World Bank (World Bank, Bangkok, 2017)
The Malaysian economy decelerated as solid domestic demand was not sufficient to offset a weakening external environment. Private consumption growth continued at a healthy pace. Favorable rubber and palm oil prices drove up incomes of smallholders while continued employment and wage growth supported urban incomes. In contrast, fixed investment was more volatile, with private investment showing signs of picking up while public investments lagged. Malaysia's overall balance of payments recorded a larger surplus in the first half of the year reflecting a widening current account surplus and substantial net financial inflows. Malaysia's open economy is expected to slow further in the remainder of 2011 and into early 2012 mainly due to the deterioration in the outlook for external demand. Cities are central to Malaysia's aspiration to become a high-income economy. Smart cities are skilled and innovative. They play a crucial role in catalyzing economic growth by generating productivity gains through agglomeration economies. Smart cities are green and sustainable. They ensure a high quality of life to all citizens and the sustainability of economic gains. Finally, smart cities are resilient.